Identification of Dermatophytes Causing Tinea Unguium in Fisherman in Tanah Lemo Subdistrict - Asdinar, Asdinar; Ananda, Alya; AB, Aszrul (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2024)
Nail infection or tinea unguium is a disease caused by dermatophyte fungi and often occurs in fisherman due to their activities in wet environments without protection such as gloves or boots. Common symptoms found include nail damage, thickening, nail lifting, uneven broken nails, loss of shine, and discoloration to yellow, brown, or black. This study aims to identify the types of dermatophyte fungi that cause tinea unguium in fisherman in Tanah Lemo Village. This study used a qualitative approach with a fungal culture method using Saboraud Dextrose Agar (SDA) media and microscopic examination using 10% KOH solution. The study population was 115 fisherman, with samples of 25 people taken from their nails through macroscopic and microscopic examination methods. The results showed that a wet and dirty work environment is a major risk factor for fungal infections in fisherman's nails. The implication of this study is the importance of prevention efforts through education on the use of personal protective equipment, such as gloves and boots, to reduce the risk of fungal infections. Additional factors such as the length of exposure to wet environments also affect fungal growth, so better risk management of the work environment is needed.